When Digital Marketing Meets e-WOM: Understanding How Purchase Intention Shapes Consumer Decisions at Wahyu Redjo Jewelry, Kediri - Mustikasari, Teti Agustin; Kurniawan, Brahma Wahyu (Yayasan Riset dan Pengembangan Intelektual, 2025)
In this study , Gold jewelry plays a dual role in Indonesia, serving both aesthetic and symbolic functions as a marker of social status and as a reliable investment asset. With the digital transformation, consumer behavior especially among Millennials and Generation Z has shifted significantly: they increasingly rely on online information regarding price, product quality, and brand reputation before committing to a purchase. This study examines factors affecting purchase intention and actual purchase decision at Wahyu Redjo Jewelry’s new store in Kediri, with emphasis on digital marketing strategies and electronic word of mouth (e-WOM). Data were collected via a structured survey of potential customers and analysis of customer reviews. Findings indicate that both strong digital marketing presence and favorable e-WOM significantly enhance purchase intention, which in turn highly correlates with purchase decision. These results suggest that Wahyu Redjo should intensify its digital engagement and leverage positive consumer testimonials to build trust and competitiveness in the local Kediri market